Computation of Sanskruti Index of Certain Interconnection Networks - Saeed, Muhammad; Iinran, Muhammad; Rehman, Noor (Utilitas Mathematica, 2019)
The molecular topological indices are the numerical invariants associated to a molecular graph and are vital to predict their bioac-tivity. These indices are studied and used in mathematical chemistry, pharmaceuticals, drug designs, and in other areas of science. The Sanskruti index denoted by S(G) shows a good correlation with entropy of an octane isomers. In this article, we compute Sanskruti index for certain discrete dynamical systems like silicate network, hex derived network, hexagonal network, honeycomb network, chain silicate network, oxide network, copper oxide, and subdivision of copper oxide by using the edge partition technology and combinatorial computing. Furthermore, we give closed results of S(G) index. We give analytical closed formula for the above interconnection networks. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.